Severe alveolar bone resorption in Felty syndrome: a case report - Satoru Morikawa; Yoko Miyashita; Mana Nasu; Shunichi Shibazaki; Satoshi Usuda; Kazuyuki Tsunoda; Taneaki Nakagawa (Journal of Medical Case Reports, 2022)
Abstract Background Felty syndrome is defined by three conditions: neutropenia, rheumatoid arthritis, and splenomegaly. Neutropenia associated with pancytopenia may further affect the dental condition of a patient. Periodontal treatment and surgery in patients with Felty syndrome necessitates cooperation with a hematologist. Here we present a case of a patient with Felty syndrome who was initially referred to the oral surgery hospital attached to the School of Dentistry for extensive periodontitis. She was effectively treated in collaboration with the hematology department. Case presentation A 55-year-old Asian woman visited our department with concerns of worsening tooth mobility, discomfort, and spontaneous gingival bleeding. Initial periodontal examination revealed generalized severe periodontitis (Stage IV Grade C) resulting from leukopenia/neutropenia and poor oral hygiene. A thorough treatment strategy involving comprehensive dental procedures, such as multiple extractions and extensive prosthetic treatment, was implemented. Following the diagnosis of Felty syndrome, the patient was started on treatment with oral prednisolone 40 mg/day, which effectively controlled the disease. Furthermore, there was no recurrence of severe periodontitis after the periodontal treatment. Conclusions Dentists and physicians should be aware that immunocompromised individuals with pancytopenia and poor oral hygiene are at risk of developing extensive periodontitis. If their susceptibility to infection and pancytopenia-related bleeding can be managed, such patients can still receive comprehensive dental treatment, including teeth extractions and periodontal therapy. Cooperation among the dentist, hematologist, and patient is necessary to improve treatment outcomes and the patient’s quality of life.